Law, religion and human dignity in the Muslim world today: an examination of IOC's Cairo Declaration on human rights - Ahsan, Abdullahil (Center for the Study of Law and Religion at Emory University, 2008)
Human dignity is the recognition and respect of human need, desire and expectation one individual by another. This recognition is indispensable because no human being survives alone: Human dignity creates the foundation of society and civilization. Our knowledge of history suggests that religious ideas have provided this basic foundation of civilization. Describing the first recognized civilization in history one historian says, “Religion permeated Sumerian civic life.” According to another historian, “Religion dominated, suffused, and inspired all features of Near Eastern society—law, kingship, art, and science.” Based on these observations while defining civilization Samuel Huntington asserts, “Religion is a central defining characteristic of civilizations.” In Islam, the Qur’an declares that: “We have bestowed dignity on the progeny of Adam.” The verse then continues to remind the whole of mankind of God's special favor unto them with physical and intellectual abilities, natural resources and with superiority over most other creatures in the world. This dignity is bestowed through God's act of creating Adam and breathing into him His Own Spirit. Since all human beings originated from Adam and his spouse, every single human being possesses this dignity regardless of color, race, religion and tribe. The whole of mankind, as khalīfah (vice-resenf) is responsible for establishing peace on earth through divinely ordained values such as amānah (trust), ‘adālah (justice) and shūra (consultation).